2020
DOI: 10.3390/ijms21124444
|View full text |Cite
|
Sign up to set email alerts
|

Fyn Tyrosine Kinase as Harmonizing Factor in Neuronal Functions and Dysfunctions

Abstract: Fyn is a non-receptor or cytoplasmatic tyrosine kinase (TK) belonging to the Src family kinases (SFKs) involved in multiple transduction pathways in the central nervous system (CNS) including synaptic transmission, myelination, axon guidance, and oligodendrocyte formation. Almost one hundred years after the original description of Fyn, this protein continues to attract extreme interest because of its multiplicity of actions in the molecular signaling pathways underlying neurodevelopmental as well as neuropatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 225 publications
(344 reference statements)
3
48
0
Order By: Relevance
“…The increase in APP Tyr phosphorylation was analysed with respect to the basal APP expression levels in the total lysate of each sample ( Figure 1 , Figure 2 , Figure 3 and Figure 4 ). In addition, the Fyn Tyr 420 phosphorylation was also assessed as an indirect measure of Fyn TK activity [ 13 ], and the results were normalised on Fyn basal expression levels ( Figure 1 , Figure 2 , Figure 3 and Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in APP Tyr phosphorylation was analysed with respect to the basal APP expression levels in the total lysate of each sample ( Figure 1 , Figure 2 , Figure 3 and Figure 4 ). In addition, the Fyn Tyr 420 phosphorylation was also assessed as an indirect measure of Fyn TK activity [ 13 ], and the results were normalised on Fyn basal expression levels ( Figure 1 , Figure 2 , Figure 3 and Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed the potential role of APP Tyr 682 phosphorylation as a biomarker for APP dysregulation in trafficking and processing, and as a predictive factor for the increased production of neurotoxic Aβ peptide and neurodegenerative processes [ 2 , 3 , 5 , 6 , 7 , 8 , 9 , 10 , 13 , 15 ]. Indeed, the dysregulation of kinase activity has been associated with the progression of other neurodegenerative diseases, and has been proposed as a potential biomarker for other major proteinopathies besides AD, including PD [ 16 , 17 , 18 ] and Huntington’s disease [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fyn has a complex molecular structure that consists of a unique N-terminal sequence and three protein modules: Src-homology-3 (SH3) module (an interaction domain that is specialized for the recognition of xPxxP sequence motifs), Src-homology-2 (SH2) module, which recognizes pTyr, and the catalytic domain, which binds and cleaves adenosine triphosphate and mediates Tyr phosphorylation in protein targets. Intramolecular interactions that involve the SH3 and SH2 domains contribute to the negative regulation of Fyn kinase activity [36,[54][55][56][57][58][59].…”
Section: Fe65 Promoted Fyn Mediated App Tyr682 Phosphorylation In Hummentioning
confidence: 99%
“…FYN is primarily in several transduction pathways in the central nervous system, such as axon guidance, myelination, and oligodendrocytes formation. FYN regulates mechanisms related to learning and memory processes and is attributed to the development of several neurological disorders including Alzheimer's disease and multiple sclerosis [32]. Grant et al found that fyn mutant mice showed impaired spatial learning, which further illustrates that FYN may involve the core process of the growth of neurons in the developing hippocampus [33].…”
Section: Discussionmentioning
confidence: 99%